Aboriginal student strength to persist and Indigenous Knowledges in community colleges. Issue 1 (9th February 2015) - Erwin, Elizabeth; Muzzin, Linda
Abstract : Purpose: – The purpose of this paper is to document experiences of Aboriginal students in community colleges from the perspective of Aboriginal communities rather than policymakers and shows how these communities support student persistence in college. Design/methodology/approach: – Interviews with 16 Aboriginal college students, staff and community members were undertaken with Aboriginal guidance, and analysis was undertaken informed by the writings of Aboriginal scholars. Findings: – The major finding was that First Nations students experience a disconnect between the epistemology of Aboriginal peoples and ways of being in community colleges. Most demonstrate bravery and persistence in their studies as well as resistance to assimilation. Understanding and support is provided by surrounding Aboriginal communities, based on their appreciation of the epistemological roots of the problem. Practical implications: – Frequent reference to the absence of Indigenous Knowledges suggests that more must be done to make Aboriginal students feel safe in colleges where they are in the minority. In view of their feeling of "disconnect, " safe Aboriginal centers, or "homes away from home" are one of many ways to support these students. Originality/value: – The research challenges assimilationist approaches to Aboriginal college students, and highlights supporting Indigenous peoples, as described in global terms by Indigenous scholars.